Torque de inserção e força de arrancamento de mini-implantes ortodônticos - Kitahara-céia, Flávia Mitiko Fernandes (2009)
Introduction: Different configurations of mini-implants screw can influence the torque of insertion, the pullout strength and consequently, the primary stability. The objective was to evaluate the insertion torque and pullout strength of five types of mini-implants. Material and Method: Were obtained images of the mini-implants active points (STEMI 2000-C and MEV) and analyzed by the Axio Vision program (Zeiss, Jena, Germany). Five mini-implants in each group: NEO(Neodent), SIN, CON (Connection), DEN (Dentaurum) and RMO were inserted into porcine rib and the insertion torque recorded by the Lutron 101 software. The tensile test was carried out in the Universal Machine Emic DL 10000 (100kgf/0.05mm/sec). Results: The torque of insertion ranged from 6.40 Ncm to 14.60 Ncm, with a statistically significant difference between groups and RMO DEN, and DEN, CON, NEO and CON; and NEO and RMO. The pullout strength ranged between 136.45 N and 227.30 N, and there was no statistically significant difference between groups. Conclusions: Different mini implants showed active spikes with different characteristics. The torque of insertion was directly proportional to the number of threads and inversely to the fillet angle and bottom of the threads (p<0.05). The structural features of mini-implants did not affect the pullout strength, with no difference between groups (p> 0.05).